Uma análise comparativa entre power BI e Google Data Studio análise preditiva empresarial. - MORAES, Thiago Palomares de; NARDOTTO, João Vitor Alvim (275, 2024)
O estudo compara as ferramentas de Business Intelligence (BI) Power BI e Google Looker, aplicadas à Análise Preditiva para melhorar a Previsão de Demanda no setor de padaria de um supermercado. A pesquisa utilizou dados de vendas e mix de produtos, identificando padrões de consumo com as plataformas. O Power BI se destacou pela facilidade de uso, enquanto o Google Looker oferece mais flexibilidade, mas exigiu maior conhecimento técnico. A Análise Preditiva sugeriu ajustes no mix de produtos para melhorar a rotatividade e a lucratividade.

The study compares the Business Intelligence (BI) tools Power BI and Google Looker, applied to Predictive Analytics to improve Demand Forecasting in the bakery sector of a supermarket. The research used sales and product mix data, identifying consumption patterns with the platforms. Power BI stood out for its ease of use, while Google Looker offered more flexibility but required more technical knowledge. Predictive Analytics suggested adjustments to the product mix to improve turnover and profitability.
A comparative analysis between power bi and google data studio business predictive analysis.
Keywords: Supermercado; Ferramentas; Informação e Comunicação